The Need for Juvenile Parenting Services with Authoritarian Parents: The Prevention Concept of Bullying Attitude - Ikawati, Ikawati (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This study is aimed to determine the relationship of authoritarian parent attitudes with the teenagers’ tendency of behaving bullying. The research was conducted in Yogyakarta Special Region. The subjects of the research were determined purposively by the following criteria: male or female adolescents, in the age range from 12 to17 years old, resided in Yogyakarta, with the education background of junior high school or that of equivalent, and had complete parents. Data collection techniques were carried out through questionnaire distribution to 30 respondents and the objects of research were the authoritarian parents’ attitudes and that of teenagers’ tendency to behave bullying. The result of the research was measured and calculated by using product Moment program of SPS Sutrisnohadi (2000) version with the rxy value result of 0,463 with p = 0,019 and determination coefficient of 0,309. These results can be concluded that the contribution of authoritarian parents’ attitudes toward the teenagers’ tendency to behave bullying is at 30.9 percent. It means that the teenagers’ tendency to behave bullying is at 30.9 percent by having authoritarian parents. Based on the research results, it is recommended to the Ministry of Social RI through the Directorate of Family Empowerment and Social Institution to improve its programs through family strengthening (such as parenting pattern / good parents’ attitude) in order to build up children’ potentiality as potential future generation so that later they are able to either become smart and qualified human resources and posses good moral intelligence. It is also recommended that parents behave attentively and compassionately and do not impose their will to their children. In this way, children may develop themselves to be having morality, responsible, intelligent and qualified human resources and so that they can prevent the tendency to behave bullying attitude.